Towards person-centred quality care for children with life-limiting and life-threatening illness: Self-reported symptoms, concerns and priority outcomes from a multi-country qualitative study. (March 2020) - Namisango, Eve; Bristowe, Katherine; Murtagh, Fliss EM; Downing, Julia; Powell, Richard A; Abas, Melanie; Lohfeld, Lynne; Ali, Zipporah; Atieno, Mackuline; Haufiku, Desiderius; Guma, Samuel; Luyirika, Emmanuel BK; et al.
Background: Paediatric life-limiting and life-threatening conditions (life-limiting conditions) place significant strain on children, families and health systems. Given high service use among this population, it is essential that care addresses their main symptoms and concerns. Aim: This study aimed to identify the symptoms, concerns and other outcomes that matter to children with life-limiting conditions and their families in sub-Saharan Africa. Setting and participants: Cross-sectional qualitative study in Kenya, Namibia, South Africa and Uganda. Children/caregivers of children aged 0–17 years with life-limiting conditions were purposively sampled by age, sex and diagnosis. Children aged 7 and above self-reported; caregiver proxies reported for children below 7 and those aged 7 and above unable to self-report. Results: A total of 120 interviews were conducted with children with life-limiting conditions ( n = 61; age range: 7–17 years), and where self-report was not possible, caregivers ( n = 59) of children (age range: 0–17) were included. Conditions included advanced HIV (22%), cancer (19%), heart disease (16%) endocrine, blood and immune disorders (13%), neurological conditions (12%), sickle cell anaemia (10%) and renal disease (8%). Outcomes identified included physical concerns – pain and s ymptom distress; psycho-social concerns – family and social relationships, ability to engage with age-appropriate activities (e.g. play, school attendance); existential concerns – worry about death, and loss of ambitions; health care quality – child- and adolescent-friendly services. Priority psycho-social concerns and health service factors varied by age. Conclusion: This study bridges an important knowledge gap regarding symptoms, concerns and outcomes that matter to children living with life-limiting conditions and their families and informs service development and evaluation.